2016
DOI: 10.1121/1.4942390
|View full text |Cite|
|
Sign up to set email alerts
|

Personal and situational variables associated with wind turbine noise annoyance

Abstract: The possibility that wind turbine noise (WTN) affects human health remains controversial. The current analysis presents results related to WTN annoyance reported by randomly selected participants (606 males, 632 females), aged 18-79, living between 0.25 and 11.22 km from wind turbines. WTN levels reached 46 dB, and for each 5 dB increase in WTN levels, the odds of reporting to be either very or extremely (i.e., highly) annoyed increased by 2.60 [95% confidence interval: (1.92, 3.58), p < 0.0001]. Multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 38 publications
8
69
0
Order By: Relevance
“…In their estimation of the burden of disease from environmental noise exposure, the WHO regional office for Europe has assigned a "conservative" disability weight of 0.02 to long-term high (transportation) noise annoyance, where 0 is equivalent to ideal health and 1 is equivalent to death [16]. Although a statistical association was found between high WTN annoyance and several reported and measured health endpoints in the CNHS, these were unrelated to the level of WTN exposure, and there is no way of determining if these conditions may have either pre-dated, and/or were possibly exacerbated by, exposure to wind turbines [1][2][3]7]. The extent to which long-term high noise annoyance may impact one's health is uncertain.…”
Section: Despite An Increase In Annoyance the Cnhs Concluded No Advementioning
confidence: 99%
See 1 more Smart Citation
“…In their estimation of the burden of disease from environmental noise exposure, the WHO regional office for Europe has assigned a "conservative" disability weight of 0.02 to long-term high (transportation) noise annoyance, where 0 is equivalent to ideal health and 1 is equivalent to death [16]. Although a statistical association was found between high WTN annoyance and several reported and measured health endpoints in the CNHS, these were unrelated to the level of WTN exposure, and there is no way of determining if these conditions may have either pre-dated, and/or were possibly exacerbated by, exposure to wind turbines [1][2][3]7]. The extent to which long-term high noise annoyance may impact one's health is uncertain.…”
Section: Despite An Increase In Annoyance the Cnhs Concluded No Advementioning
confidence: 99%
“…The strengths of the CNHS are as follows: (1) large randomly selected sample of participants (n = 1238), (2) high response rate (78.9%) that did not vary by proximity to wind turbines in either province, (3) broadly scoped questionnaire, (4) inclusion of objectively measured endpoints of stress, blood pressure, heart rate and sleep, (5) calculated WTN levels validated with representative field measures, and (6) an exposure-response analysis that encompassed a greater than 21 dB range of exposure to WTN. Despite these strengths, no single cross-sectional study should be viewed as conclusive, and all studies have some limitations.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Noise pollution, especially in the urban environment, is on the increase [6][7][8] and ranks among the environmental stressors with the highest public health impact [8]. The auditory effects include hearing impairment and permanent hearing loss due to excessive noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…According to Schomer et al (2012): "CTL value corresponds to the DNL value at which half of the people in a community describe themselves as highly annoyed by noise exposure." Michaud et al (2016b) reported CTL values regarding outdoor noise annoyance for several studies. CTL values for indoor noise annoyance have not been reported in the studies of Table I.…”
mentioning
confidence: 99%
“…The studies agree that noise annoyance increases with increasing sound level. However, new research is important because different exposure-response relationship have been obtained from different countries and even from different provinces of, e.g., Sweden (Pedersen andPersson Waye, 2004, 2007) and Canada (Michaud et al, 2016a(Michaud et al, , 2016b.…”
mentioning
confidence: 99%